OBSERVATION ON ECOLOGY AND DIVERSITY OF PERIPHYTON COMMUNITY IN THE MAL GAD STREAM FROM GARHWAL REGION, INDIA - BAHUGUNA, PANKAJ; RAJANI, .; RAYAL, RAJESH; BALUNI, PRATIBHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The current research focuses on the periphytic diversity of the Mal Gad stream in Uttarkashi, Uttarakhand, India. The coordinates of this spring-fed stream are Latitude: 30°52'38.25"N and Longitude: 78°4'11.49"E. During the investigation it was found that the periphytic algal diversity of Mal Gad stream was represented by 19 genera belonging to 3 major classes namely Bacillariophyceae (Cymbella sp., Synedra sp., Navicula sp., Fragilaria sp., Gomphonema sp., Achnanthes sp., Bacillaria sp., Diatoma sp. and Tabellaria sp.), Chlorophyceae (Oedogonium sp., Spirogyra sp., Microspora sp., Volvox sp., Zygenema sp., Cladophora sp., Geminela sp., and Ulothrix sp.) and Cyanophyceae (Nostoc sp. and Rivularia sp,). The present investigation will be helpful in enhancing the knowledge regarding the production potential of the water body. The dominance of Bacillariophyceae indicates the healthy ecological condition of the stream. Based on the study, the stream is found favorable for the culture of herbivorous snow-trout, Schizothorax sp. on a commercial scale.